Compatible solutes mitigate damaging effects of salt stress by reducing the impact of stress-induced reactive oxygen species - Cuin, Tracey Ann; Shabala, Sergey (Plant signaling & behavior, 2008)
Under abiotic stress conditions, rapid increases in reactive oxygen species (ROS) levels occurs within plant cells. Although their role as a major signalling agent in plants is now acknowledged, elevated ROS levels can result in an impairment of membrane integrity. Similar to our previous findings on imposition of salt stress, application of the hydroxyl radical (OH * ) to Arabidopsis roots results in a massive efflux of K + from epidermal cells. This is likely to cause significant damage to cell metabolism. Since K + loss also occurs after salt application and salt stress leads to increased cellular ROS levels, we suggest that at least some of the detrimental effects of salinity is due to damage by its resulting ROS on K + homeostasis. We also observed a comparative reduction in K + efflux by compatible solutes after both oxidative and salt stress. Thus, we propose that under saline conditions, compatible solutes mitigate the oxidative stress damage to membrane transporters. Whether this amelioration is due to free-radical scavenging or by direct protection of transporter systems, warrants further investigation.